Frequently asked questions on consulting services. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This document aims to capture and disseminate knowledge on consultant selection procedures, based on experiences in ADB financed projects in India and issues raised in trainings organized by ADB India Resident Mission Capacity Development Resource Center.
Keywords: Consulting services; Asian Development Bank; Electronic book